GAS-CHROMATOGRAPHIC MEASUREMENTS OF ATMOSPHERIC METHANE AT SYOWA STATION IN 1983,AND BETWEEN TOKYO AND SYOWA STATION LATE IN 1984 - ヒロタ, ミチオ; ムラヤマ, ハルタ; マキノ, ユキオ; ムラマツ, ヒサフミ; HIROTA, Michio; MURAYAMA, Haruta; MAKINO, Yukio; MURAMATSU, Hisafumi (National Institute of Polar Research, 1987)
P(論文) Atmospheric methane was measured by a gas-chromatographic method. Air samples were collected at Syowa Station in 1983,and on board between Tokyo and Syowa Station late in 1984. Mixing ratios at Syowa Station showed some seasonal variation and were in good agreement with those at Mawson Station. Mixing ratio decreased gradually from 30 to 5°N, and steeply between 5°N and the equator. In the Southern Hemisphere, mixing ratios were almost constant between the equator and 66°S. The mean value was 1.577ppm and the standard deviation was 0.008ppm. departmental bulletin paper